Struktura społeczna mieszkańców województwa łódzkiego w świetle powszechnych spisów ludności z 1921 i 1931 r. - Rzepkowski, Arkadiusz (Przegląd Nauk Historycznych, 2012)
The structure of Polish population in the interwar period has been already presented by scholars dealing with this issue, mainly in publications of Janusz Żarnowski. However, there is a need for determining the social composition of inhabitants of particular voivodeships of Second Polish Republic. This article in an attempt to present this social stratification in Łódź Voivodeship on the basis of censuses done in 1921 and 1931. Publications on Łódź Voivodeship during the period of Second Polish Republic are yet to be written, partly because the attention of researchers was focused mainly on the capital of the voivodeship – the city of Łódź. Although Łódź Voivodeship was one of the most industrialized voivodeships of the interwar period Poland, the majority of its population was employed in agriculture and related branches of economy. Because of that the population structure of Łódź Voivodeship during the interwar period was a typical one for a voivodeship of an agricultural and industrial nature. During that time a large part of the population of the voivodeship was economically independent and conducted business activity, they were mostly small business owners, which is typical for capitalistic societies of the first half of 20th century in Central and Eastern Europe. Another characteristic feature of this voivodeship was the fact that a substantial percentage of population worked as hired labor, especially doing manual tasks in big factories, thus a high percentage of workers and home workers, especially in regions of concentrated industry.